ECONOMIC ANALYSIS OF THE ACTIVITY OF SMALL BUSINESS SUBJECTS IN NAMANGAN REGION - Alimatova Shoxsanam (Scholars Digest Publishing, 2023)
This article discusses the concept of the formation of competitiveness of small businesses and its essence, as well as the concept of Competitiveness, about such aspects as competitive advantage, price competition, strategic management and other historical and sociocultural aspects, and Competitiveness, as well as an independent variable, intermediate a variable depending on the approach in the study or considered as a completely dependent variable, consisting of different heterogeneous factors depending on the field of activity, and the competitiveness of small and medium-sized hotels in the hotel sector, a comparison is presented with their competitors in terms of price, quality of service, gross margin, planning and achieving business goals.
Keywords: This article discusses the concept of the formation of competitiveness of small businesses and its essence, as well as the concept of Competitiveness, about such aspects as competitive advantage, price competition, strategic management and other historical and sociocultural aspects, and Competitiveness, as well as an independent variable, intermediate a variable depending on the approach in the study or considered as a completely dependent variable, consisting of different heterogeneous factors depending on the field of activity, and the competitiveness of small and medium-sized hotels in the hotel sector, a comparison is presented with their competitors in terms of price, quality of service, gross margin, planning and achieving business goals.